Ignoring environmental change? On fishing quotas and collapsing coastlines in Bykovskiy, Northern Sakha (Yakutiya) - Povoroznyuk, Olga; Schweitzer, Peter (Ambio, 2023)
The Indigenous village of Bykovskiy is located 40km from Tiksi, the administrative center of Bulunskiy District (Ulus), in the northern part of the Republic of Sakha (Yakutiya), Russia. Founded as a Soviet fishing cooperative, it became home to Indigenous Sakha, Evenkis, Evens, as well as to Russian settlers and political prisoners from the Baltic states. Post-Soviet transformations, coupled with escalating environmental change processes, has been altering the local economy and subsistence activities since the 1990s. Although our interlocutors directly observed and experienced such changes, they seemed to ignore the visible problem of severe coastal erosion that was destroying a local cemetery. This article is based on ethnographic fieldwork conducted in the study region in 2019, and combines approaches from the anthropology of climate change with reception and communication studies. It examines “ignorance” as a strategy of adaptation to multiple stressors under historically reproduced colonial structures of governance.